Reliability and Construct Validity of the Malay Version of the Cyclist Motivation Instrument (CMI) - Cheah, W.L; Helmy, Hazmi; Razali Lukas, Emmanual R; Joannes, Irvy; Berry, Jaeverny H; Lim, Luther (Cycling Research Center, 2014)
With increasing interest in cycling, there is a need to understand what motivates cyclists to cycle. The Cyclist Motivation Instrument (CMI) has been shown to be a valid and reliable instrument to measure the motivation factors elsewhere. The present study was to assess the reliability and construct validity of the Malay version of the Cyclist Motivation Instrument among cyclists in Kuching, Sarawak, Malaysia. A total of 180 cyclists consented to participate in the study and were given the Malay version of the CMI to complete. Back translation method was used to ensure the face validity of the questionnaire. Reliability was determined using Cronbach’s alpha for internal consistency. Construct validity was assessed using exploratory factor analysis. The internal consistency for all components was satisfactory with Cronbach’s alpha coefficients of 0.799 to 0.880 and therefore confirmed the adequacy of these components. Exploratory factor analysis using Principal Component Analysis with a Varimax rotation showed 32 items were loaded into six factors orthogonal solution with 67.8% of the variance. In conclusion, all components of CMI were found to be reliable and valid for determining factors motivating cyclists to cycle.